2004
DOI: 10.1097/00004872-200411000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Tempol augments angiotensin II-induced AT2 receptor-mediated relaxation in diabetic rat thoracic aorta

Abstract: The results suggest enhanced AT2-receptor density and function [mediated by a nitric oxide and ATP-sensitive K channel-dependent relaxation response (in presence of an AT1 receptor blocker)] in thoracic aorta isolated from diabetic rats. This could be a compensatory mechanism, which may be therapeutically exploited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Cosentino et al (2005) suggested that the losartan-unmasked AT 2 receptor-mediated vasodilatation seen in the aorta isolated from SHR may contribute to the beneficial hemodynamic effects of AT 1 receptor blockade. Arun et al (2004) noted that ANG IIinduced relaxation, evident only in the presence of the AT 1 blocker, was enhanced in aortic rings isolated from diabetic rats but not control rats, the response being attenuated by L-NAME or ATP-sensitive K ϩ channel blockers and abolished by treatment with both inhibitors. [ 3 H]ANG II saturation binding at the AT 2 receptor was enhanced in aortic membranes from diabetic rats compared with control rats.…”
Section: Angiotensin-induced Endothelium-derived Relaxing Factomentioning
confidence: 99%
“…Cosentino et al (2005) suggested that the losartan-unmasked AT 2 receptor-mediated vasodilatation seen in the aorta isolated from SHR may contribute to the beneficial hemodynamic effects of AT 1 receptor blockade. Arun et al (2004) noted that ANG IIinduced relaxation, evident only in the presence of the AT 1 blocker, was enhanced in aortic rings isolated from diabetic rats but not control rats, the response being attenuated by L-NAME or ATP-sensitive K ϩ channel blockers and abolished by treatment with both inhibitors. [ 3 H]ANG II saturation binding at the AT 2 receptor was enhanced in aortic membranes from diabetic rats compared with control rats.…”
Section: Angiotensin-induced Endothelium-derived Relaxing Factomentioning
confidence: 99%
“…12 We have shown previously that the balance between NO and cyclooxygenase (COX) derivatives is modified in hypertension 13 and may involve the inducible form of the enzyme, COX-2. 14 Thus, in this study, we investigated the possible roles of ROS and COX-2 in alterations of AT2R-dependent dilation in resistance arteries from type 2 diabetic rats.…”
mentioning
confidence: 99%
“…Ang II plays a fundamental role in controlling the functional and structural integrity of arterial wall and contributes significantly to the pathological mechanisms underlying vascular complications of diabetes (1,2,11,87). Recent studies suggest that cardiac myocytes and vascular smooth muscles contain RAS, which is activated under diabetic conditions (82).…”
Section: Role Of Angiotensin II (Ang Ii) In Diabetic Vascular Complicmentioning
confidence: 99%
“…We are proposing that chronic release of Ang II leads to changes in ionic currents and action potentials and stimulates excessive collagen synthesis in human vascular smooth muscle cells and that these effects can be reversed by blocking the formation or action of Ang II. The apparent benefits of Ang II receptor blockade or ACE inhibition in diabetes are cardiac (26,70) and vascular protection (2). Ang II can activate NADPH oxidase, whose product superoxide anion (O 2 -) quenches nitric oxide (NO) resulting in peroxynitrite (ONOO -) formation (48,61).…”
Section: Role Of Angiotensin II (Ang Ii) In Diabetic Vascular Complicmentioning
confidence: 99%
See 1 more Smart Citation